Brand positioning strategy in the competitive aspect - Kraujalienė, Lidija; Kromalcas, Saulius (Business: Theory and Practice, 2022)
A new brand for an organization is inseparable from organizational identity. The aim of the research is to investigate the positioning strategy in terms of competitiveness and visitors of Kaunas District Public Library (KDPL). Research methodology: analysis of scientific literature and statistical data, staff survey, SWOT analysis. Main findings: the flow of visitors of KDPL in the period of 2018–2020 has decreased by a quarter, the user portrait consists of 5 user groups (employed, studying, pre-school children, unemployed persons and others), the number of library users by gender did not change, 70% consists of women, attendance of four user groups decreased or remained virtually unchanged, when the amount of employed users increased by about 16 percent. SWOT analysis has shown the absence of a brand positioning strategy. Qualitative study of the library competitors users’ needs and expectations can be analysed further. The local position of KDPL’s has shown the potential to grow up in Kaunas city. The originality of the paper covers individualized research on a brand positioning strategy of public sector organization, while the available research has been carried out on private branding. The current research will be useful for KDPL and other public organisations.